QUESTION BANK ON AGRICULTURE - R.K. NANWAL; R.K. NANWAL (NEW DELHI AGRI-BIOVET PRESS, 2014)
The book "Question Bank on Agriculture "covers 16 chapters on important crrent topics to refresh the knowledge of the readers.
Green revolution Fertilizer Weed their control Plant protection
Keywords: A Handbook for JRF,SRF,ARS,NET,UPSC,ASRB & allied agricultural exams -- Objective questions in various aspects